Controllable synthesis of MnO2 nanostructures anchored on graphite foam with different morphologies for a high-performance asymmetric supercapacitor. Issue 12 (1st March 2018) - Lv, Xingbin; Zhang, Hualian; Wang, Feifei; Hu, Zhufeng; Zhang, Yuxin; Zhang, Lili; Xie, Rui; Ji, Junyi
Abstract : MnO2 nanostructures with different morphologies (nanowires, nanowire bundles, flower-like nanosheet bundles) were synthesized via a simple and surfactant-free hydrothermal method. Abstract : MnO2 nanostructures with different morphologies (nanowires, nanowire bundles and flower-like nanosheet bundles) were synthesized by adjusting the concentration of KMnO4 solution using a simple and surfactant-free hydrothermal method. Both MnO2 nanowires and nanosheets have ultrathin thickness of about 10–30 nanometers. Such 'open' nanostructures can facilitate the electrolyte infiltration and increase the active material utilization efficiency. Owing to the high electron conductivity of the graphene/Ni foam (GNF) substrate as well as the large electrolyte/electrode contact interface, a specific capacitance of 201 F g −1 can be obtained in 1 M Na2 SO4 electrolyte. An asymmetric supercapacitor assembled with flower-like MnO2 nanosheet bundles on GNF and activated microwave exfoliated graphite oxide (a-MEGO) yields an energy density of 44.5 W h kg −1 and a power density of 50.0 kW kg −1, respectively. These unique and controllable MnO2 nanostructures may have enormous potential applications in the fields of energy storage and sensors.